North American Environmental Outlook to 2030 (Montreal (Quebec) Commission for Environmental Cooperation, 2010)
This report summarizes recent research concerning the major forces and underlying trends that are likely to shape the environment of North America in 2030. The intention of this report is not to present a prediction of the future. Rather, it is to consider the possibilities that the future might hold in light of the environmental and social stresses facing North America and the world at this time.
Keywords: Medio ambiente; Prospectiva; América del Norte